The Failure of New International Economic Order: a Lesson Learned - M. Ya'kub Aiyub Kadir (Yuridika, 2021)
The establishment of the New International Economic Order (NIEO) has been underpinning the development of international law. The shortcomings of this struggle should be seen as a lesson-learn to step forward in the future. It is also essential to harmonise the economic justice relationship among all countries in the world regardless the developed or the developing countries. The sustainable struggle in the world economic sphere will appear as a shout from the perceived disadvantaged countries from an economic competition in the world.  The establishment of the right to development that have been adopted in international law is a part of journey of TW struggled in international relation. The paper is simultaneously based on the perception of understanding of principles of  NIEO coupled with scepticisms toward this principles and auto criticism of that scepticism in order to be a proposal as a source of international law in future